PEMBELAJARAN STRATEGI SAPS BERBASIS MULTIREPRESENTASI UNTUK MEREMEDIASI KESALAHAN SISWA MENYELESAIKAN SOAL HUKUM NEWTON - Rahmawati, Nursuci (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to determine the effectiveness of remediation using the systematic approach to problem solving (SAPS) strategy based on multiple representations to reduce the number of errors in answering essay test about Newton?s law in X grade SMAN 4 Sungai Raya. The study used the form of one group pretest-posttest design and the research instrument used test descriptions that consist of five items. Purposive sampling is used in this study that involving 34 students XA. The other instrument in this study was concept map and student worksheets SAPS Stages. The data analysis showed the biggest errors was 100% of the students can?t draw free body diagram in pretest, and 50% of them can?t make it in posttest and average of the propotion value for each question indicator of 0,581 moderate. Learning with the systematic approach to problem solving based on multiple representations can be alternative to remediate students? error in subject material about Newton?s law.Keywords: SAPS, Multiple Representations, Students? Error.